Efektivitas Pendidikan Kesehatan Reproduksi dalam Meningkatkan Menstrual Hygiene Management (MHM) pada Remaja Putri di Madrasah Aliyah Syaikh Zainuddin Nahdlatul Wathan Anjani - Sri hardiani; Haryani Haryani; Zahida Fathiatussa’adati; Zurriyatun Thoyibah; Fidiya Rizka (LPPM STIKES Marendeng Majene, 2026)
Menstrual Hygiene Management (MHM) is an important aspect of adolescent girls' reproductive health because improper hygiene practices during menstruation can increase the risk of reproductive health problems. This study aimed to find out the effect of reproductive health education on menstrual hygiene management among teenage girls at Madrasah Aliyah Syaikh Zainuddin Nahdlatul Wathan Anjani in East Lombok. Method: This study used a true experimental design with a posttest-only control group design. The study population consisted of 285 students, with a sample of 60 respondents, including 30 in the experimental group and 30 in the control group, using a quota sampling technique. Data analysis was done using the Mann-Whitney test. The results of the Mann-Whitney test showed a p-value < 0.05, meaning there was a significant difference between the experimental and control groups. Conclusion: Reproductive health education has a significant effect on menstrual hygiene management. Among teenage girls, the experimental group showed better results compared to the control group, where the majority of respondents in the experimental group were in the good category for reproductive health education at 53.4% and menstrual hygiene management at 60.0%. Meanwhile, the control group was mostly in the fair category, with reproductive health education at 46.7% and menstrual hygiene management at 50.0%. The Mann-Whitney test results showed a p-value of < 0.05, indicating that reproductive health education effectively improves menstrual hygiene adolescent girls